APPLYING UNIVERSAL SOIL LOSS EQUATION (USLE) TO ESTIMATING SOIL EROSION AT LAM SON HEADWATER CATCHMENT - Xuan Dung, Bui; Viet Quang, Do (Journal of Forestry Science and Technology, 2017)
Erosion is an environmental phenomenon, but due to human activities this phenomenon has led to many serious problems. With the aim of protecting soil resource, as well as circumscribe damages by erosion, so the study of applying USLE on assessing soil erosion at Lam Son headwater catchment was conducted. To reach the purposes, the content of the study focus on collecting data and using USLE, ArcGis software to form rainfall map, slope coefficient and slope length map, canopy cover coefficient map. From those maps, we can form the erosion potential map and current erosion map of the study site. The result of this study show that: (1) R factor in the study area is medium fluctuating from 950 – 1050 mm and decrease from the North to the South area; (2) Main soil type in the research area is yellow-red soil on sand (Fs) with K coefficient = 0.27; (3) In general, about 65% of the area is covered by plant, C factor was 0 - 1, averaged 0.2. This is the most important factor to determine the capable of erosion, so it is necessary to have a suitable plan for exploiting and planting forest; (4) The research area has total potential erosion (level 5) up to 90% and current erosion is 89% divided equally for 3 levels (level 1, level 4 and level 5). The area of erosion tends to decrease due to good farming method and conscious of local people; (6) The results of the study are trustful because it was verified in the research area. It can be used as document for plan of land using in the research area. In addition, the local community as well as local people should focus more on planning the bare land area and modifying the crop season.